Prospects for detecting ultra-high-energy particles with FAST - James, Clancy; Bray, J.; Ekers, Ronald (2016)
The origin of the highest-energy particles in nature, the ultra-high-energy (UHE) cosmic rays, is still unknown. In order to resolve this mystery, very large detectors are required to probe the low flux of these particles - or to detect the as-yet unobserved flux of UHE neutrinos predicted from their interactions. The `lunar Askaryan technique' is a method to do both. When energetic particles interact in a dense medium, the Askaryan effect produces intense coherent pulses of radiation in the MHz--GHz range. By using radio telescopes to observe the Moon and look for nanosecond pulses, the entire visible lunar surface ($20$ million km$^2$) can be used as an UHE particle detector. A large effective area over a broad bandwidth is the primary telescope requirement for lunar observations, which makes large single-aperture instruments such as the Five-Hundred-Meter Aperture Spherical Radio Telescope (FAST) well-suited to the technique. In this contribution, we describe the lunar Askaryan technique and its unique observational requirements. Estimates of the sensitivity of FAST to both the UHE cosmic ray and neutrino flux are given, and we describe the methods by which lunar observations with FAST, particularly if equipped with a broadband phased-array feed, could detect the flux of UHE cosmic rays.